2006
DOI: 10.1074/jbc.m513377200
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Contributes to Caspase-independent Macrophage Cell Death

Abstract: Macrophage cell death plays a role in many physiological and pathophysiological conditions. Previous work has shown that macrophages can undergo caspase-independent cell death, and this process is associated with Nur77 induction, which is involved in inducing chromatin condensation and DNA fragmentation. Here we show that autophagy is a cytosolic event that controls caspase-independent macrophage cell death. Autophagy was induced in macrophages treated with lipopolysaccharides (LPSs) and the pan-caspase inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
171
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(181 citation statements)
references
References 57 publications
7
171
1
2
Order By: Relevance
“…Because suppression of autophagy results in cell death, this observation is consistent with the above in vitro results. Although TLR4 stimulation alone cannot induce cell death, it can if the pan-caspase inhibitor z-VAD-fmk is present (34,35). Under this in vitro experimental setting, a marked enhancement of macrophage cell death was observed in the absence of HMGB1 (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Because suppression of autophagy results in cell death, this observation is consistent with the above in vitro results. Although TLR4 stimulation alone cannot induce cell death, it can if the pan-caspase inhibitor z-VAD-fmk is present (34,35). Under this in vitro experimental setting, a marked enhancement of macrophage cell death was observed in the absence of HMGB1 (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…14 When caspase activity and NF-kB are blocked, full-length RIP1 is responsible for inducing TLR4-induced necrosis 56 (Figure 7a). More recently, Xu et al 57 demonstrated autophagy in macrophages following treatment with LPS/zVAD-fmk. TRIF, RIP1 and ROS production, as well as poly-(ADP-ribose) polymerase-1 (PARP) activation, seem to be involved in inducing autophagy, which contributes to caspase-independent macrophage cell death.…”
Section: Role Of Rip1 In Death Receptor Signallingmentioning
confidence: 99%
“…Inhibition of autophagy using siRNA against Beclin-1 and Atg5 reduced etoposide-induced cell death, suggesting that these cells died an autophagic cell death. Another study found that lipopolysaccharide treatment induced caspase-independent cell death in macrophages that were inhibited by siRNA-mediated knockdown of Beclin-1 or pre-treatment with 3-MA or Wortmannin [69]. In addition, treatment with hydrogen peroxide or 2-methoxyestradiol (2-ME) to inhibit Superoxide Dismutase are both known to induce apoptosis in cells [70,71], was recently shown to induce autophagic cell death in HEK293 and U87 cells [72].…”
Section: Autophagy and Programmed Cell Deathmentioning
confidence: 99%